Trajectories of maternal pre- and postnatal anxiety and depressive symptoms and infant fear: Moderation by infant sex - Saara Nolvi; David J. Bridgett; Riikka Korja; Eeva-Leena Kataja; Niina Junttila; Hasse Karlsson; Linnea Karlsson (Elsevier, 2025)
Background
Prior work has examined the links between pre- and postnatal maternal distress and infant negative affectivity; however, there is little understanding about how the continuity of infant exposure to pre- and postnatal maternal distress relates to infant development. This study investigated the continuity of maternal pre- and postnatal depressive and anxiety symptoms and their relations with infant fear among 391 mother-infant dyads. An additional aim was to consider infant sex as a moderating factor.
Methods
Maternal anxiety and depressive symptoms were measured during gestational weeks 14, 24 and 34 and 3 and 6 months postpartum. Subsequently, infant fear was measured using mother reports (IBQ-R) at 6 months and in a laboratory setting (Lab-TAB Masks episode) at 8 months. Using growth mixture modeling, a three-class model describing the course of maternal symptoms across pregnancy and the early postnatal period was identified, consisting of mothers with “Consistently Low Distress”, “Prenatal-Only Distress”, and “Consistently High Distress”.
Results
Infant girls exposed to prenatal-only maternal distress were higher in observed fear than infant boys exposed to prenatal-only distress. Infant girls exposed to consistently high distress also showed lower observed fear than their counterparts exposed to prenatal-only maternal distress.
Limitations
The main limitation of the study is the relatively small group size within the Consistently High subgroup.
Conclusions
The findings suggest that girls might be particularly sensitive to maternal distress, and that prenatal-only and continuous distress exposure are differentially related to female infant fear.